“Vulvovaginite pustular por Ureaplasma diversum em fêmeas bovinas de corte no Vale do Guaporé, Mato Grosso” - Gaeti, João Guilherme Leite Nogueira (2014)
Ureaplasma diversum has been associated with various reproductive problems in cattle, including granular vulvovaginitis, weak calves and abortion. This study was conducted in a beef herd in Middle-West region of Brazil with the objective of identifying U. diversum with possible cause of vulvovaginite pustular in heifers and their relationship with reprodutive performance in that herd. Swabs samples were taken for PCR from a total of 58 breef heifers with vulvar lesion and 76 without vulvar lesions. The frequency of the microorganism in tested animals with macroscopic lesions was 63.7% (37/58) suggesting that U. diversum can be related to pustular vulvovaginitis (p=0.001). The multivariate logistic regression showed association with U. diversum and progesterone (P4) advice utilization (p=0.001) with possible cause of vulvar lesions. These findings indicate that U. diversum should be considered a pathogen associated a pustular vulvovaginitis in heifers from Mato Grosso state and additional studies related to risk factors for P4 advice transmition must be performed